Employment effects of skills trainings in Sub-Saharan Africa: A systematic review of recent randomized controlled trials - Bernd Beber; Tabea Lakemann; Regina Schnars; Jann Lay (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This study provides a comprehensive systematic review of recent randomized controlled trials (RCTs) to evaluate the employment effects of skills training programs in sub-Saharan Africa, a region where such interventions are a key element of development assistance. The review focuses on studies conducted between 2019 and 2024, a period marked by a significant increase in the number of RCTs in this area, aiming to fill the gap left by earlier reviews which did not reflect this surge in research activity. By employing the SPIDER tool for defining search terms and the PRISMA procedure for search and selection, we systematically analyze the impact of these training programs on employment outcomes. The findings reveal a shift towards more optimistic assessments compared to previous analyses, suggesting that recent skills training programs may indeed contribute to improving employment rates and job quality. This review not only sheds light on the potential of such interventions to support Sustainable Development Goal (SDG) 8, which aims for sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all but also highlights the necessity for ongoing research to explore the conditions under which these programs can be most effective, thereby supporting efforts to achieve economic development and reduce unemployment in sub-Saharan Africa. – – Diese Studie bietet eine umfassende systematische Übersicht über neuere randomisierte kontrollierte Studien (RCTs) zur Bewertung der Beschäftigungseffekte von Qualifizierungsprogrammen in Afrika südlich der Sahara, einer Region, in der solche Interventionen ein Schlüsselelement der Entwicklungszusammenarbeit sind. Die Übersicht konzentriert sich auf Studien, die zwischen 2019 und 2024 durchgeführt wurden, einem Zeitraum, der durch einen erheblichen Anstieg der Anzahl von RCTs in diesem Bereich gekennzeichnet ist. Damit soll die Lücke geschlossen werden, die frühere Reviews hinterlassen haben, die diesem Anstieg an RCTs vorangingen. Unter Verwendung des SPIDER-Tools zur Definition von Suchbegriffen und des PRISMA-Verfahrens für die Suche und Auswahl von Studien analysieren wir systematisch die Auswirkungen dieser Ausbildungsprogramme auf Beschäftigung. Die Ergebnisse zeigen eine Verschiebung hin zu optimistischeren Einschätzungen im Vergleich zu früheren Analysen, was eventuell darauf hindeutet, dass die jüngsten Qualifizierungsprogramme tatsächlich zur Verbesserung von Beschäftigungsraten und Arbeitsplatzqualität beitragen können. Dieser Bericht beleuchtet nicht nur das Potenzial solcher Maßnahmen zur Unterstützung des Ziels für nachhaltige Entwicklung (SDG) 8, das ein nachhaltiges, inklusives und nachhaltiges Wirtschaftswachstum, produktive Vollbeschäftigung und menschenwürdige Arbeit für alle anstrebt, sondern unterstreicht auch die Notwendigkeit laufender Forschung, um die Bedingungen zu erforschen, unter denen diese Programme am effektivsten sein können.
Keywords: J24; O15; C93; I25; 330; Systematic review; skills training; randomized controlled trials; sub-Saharan Africa